2021
DOI: 10.1155/2021/5581812
|View full text |Cite
|
Sign up to set email alerts
|

Trainability of Health-Related and Motor Performance Fitness in Adults with Cystic Fibrosis within a 12-Month Partially Supervised Exercise Program

Abstract: Background. Regular physical activity plays an important role in the treatment of patients with cystic fibrosis (CF). This study is aimed at investigating the effects of a 12-month partially supervised exercise program on attributes of health-related and motor performance fitness, lung function (ppFEV1), BMI, and habitual physical activity (HPA, steps/day) in adults with CF. Methods. Attributes of health-related and motor performance fitness were examined at the beginning (T0), after 6 (T1), and 12 months (T2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…In a paper published by our research group on CFmobil with adults with CF, we also observed an increase in the drop-out rate at the end of the supervised program [20]. To date, few studies have examined the effects of partially supervised exercise programs on participation [13].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In a paper published by our research group on CFmobil with adults with CF, we also observed an increase in the drop-out rate at the end of the supervised program [20]. To date, few studies have examined the effects of partially supervised exercise programs on participation [13].…”
Section: Discussionmentioning
confidence: 55%
“…The study was designed as a pre-experimental study one-group pre-test-post-test intervention study [20]. Anthropometric and pulmonary function data, physical performance data, and habitual physical activity data were collected at three different time points: baseline = T1, at the end of the monitored exercise program after six months (T3), and after further six months without monitoring (T4).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple research studies have substantiated the positive impacts of physical exercise on mental well-being ( Dai and Menhas, 2020 ; Duncan et al, 2020 ; Saqib et al, 2020 ). Moreover, a positive correlation exists between increased levels of daily exercise, also known as habitual physical activity (HPA), and enhanced aerobic performance and an extended lifespan ( Ma et al, 2021 ; Welsner et al, 2021 ). Consistent participation in physical activity yields enhancements in both bodily and mental well-being, with the adoption of additional health-enhancing practices and reduced susceptibility to chronic ailments ( Saqib et al, 2020 ).…”
Section: Hypothesis Operationalizationmentioning
confidence: 99%
“…The CFmobil project was a partially supervised physical activity intervention for pwCF aged ≥ 6 years, which has been described in detail elsewhere. The project was carried out between 2014 and 2018 at the Christine Herzog Centrum Ruhr (CHCR) and the participating hospitals (Ruhrlandklinik and Kinderklinik, Essen, Germany, and University Hospital for Paediatrics and Adolescent Medicine, Bochum, Germany) [19,20]. In the present study, pwCF aged ≥ 18 years from the University Hospital Essen (Ruhrlandklinik and Kinderklinik, Essen, Germany) and the University Hospital for Pediatrics and Adolescent Medicine (Bochum, Germany) agreed to continue participating.…”
Section: Patients and Study Designmentioning
confidence: 99%